ANALYSIS OF GENERIC STRUCTURE IN WRITING DESCRIPTIVE TEXT AT THE NINTH GRADE STUDENTS OF SMPN 3 RAMBAH HILIR - Yuniarti, Yuyun; Rahayu, Pipit; -, Eripuddin (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
Purpose of this research was to analyze the generic structure of descriptive text that writen by students of SMPN3 Rambah Hilir. in collecting the data, the researcher used the writing test. The results showed that studentsskills in generic structure of writing descriptive text at SMPN 3 Rambah Hilir as follows: 3 students (6%)wasgood categories, 32 students (30%) wasfaircategory, and 15 students (64%) was poor cate